2018
DOI: 10.4239/wjd.v9.i6.92
|View full text |Cite
|
Sign up to set email alerts
|

Iranian healthcare professionals’ perspectives about factors influencing the use of telemedicine in diabetes management

Abstract: AIMTo identify factors influencing the use of telemedicine in diabetes management from the perspectives of healthcare professionals.METHODSThis was a quantitative study that was conducted in 2016. The participants were 240 nurses and 55 physicians from three teaching hospitals as well as from one endocrinology and metabolism research center. No sampling method was used and the data were collected by using a five-point (1 to 5) Likert scale questionnaire, which had 37 questions. Descriptive and inferential stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…These insights complement the existing literature that pinpointed the importance of organizational and workflow factors that can considerably hinder mHealth adoption if not addressed properly [6,54,57]…”
Section: Discussionsupporting
confidence: 66%
“…These insights complement the existing literature that pinpointed the importance of organizational and workflow factors that can considerably hinder mHealth adoption if not addressed properly [6,54,57]…”
Section: Discussionsupporting
confidence: 66%
“…The significance of fulfilling the implementation of safety strategies and procedures in telemedicine was affirmed in several studies [21][22]. In this manner, our outcomes were in accordance with the results of previous studies, for example Kamal's study showed that physicians in Pakistan believed that keeping up the privacy of patient data and also the documentation were the most significant elements to set up a protected system for telemedicine [6].…”
Section: Discussionsupporting
confidence: 88%
“…TM technology related factors like perception towards privacy and security [17,20,21]. Organizational factors such as training, technical staff, or support were found to affect the readiness of professionals [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%